Materiality in financial reporting : an integrative perspective - Bellandi, Francesco (Emerald Publishing Limited, 2017)
Financial reporting is a strategic means of communication: management has an opportunity to interpret, and the power to deliver, what is materially important to the organization's stakeholders. Understanding materiality means steering the company in the right direction, and many internal management battles regarding what and how to disclose in external financial reporting run on the verge of materiality. This book offers an integrated perspective of materiality from the angles of accounting (IFRS, US GAAP and SEC Rules and Regulations), auditing, internal control over financial reporting, management commentary, financial analysis, management control, forensic analysis, sustainability reporting, corporate responsibility, assurance standards, integrated reporting, and limited legal considerations. In Materiality in Financial Reporting: An Integrative Perspective, the author adopts a practical, operational approach to show how strategy, processes, and communication can be used to devise a consistent corporate governance system of materiality.